CO2 Hydrogenation to Olefin-Rich Hydrocarbons Over Fe-Cu Bimetallic Catalysts: An Investigation of Fe-Cu Interaction and Surface Species - Wang, Wenjia; Wang, Xiaoxing; Zhang, Guanghui; Wang, Ke; Zhang, Fu; Yan, Tianyu; Miller, Jeffrey T.; Guo, Xinwen; Song, Chunshan (Frontiers in Chemical Engineering, 2021)
Previously, we reported a strong Fe-Cu synergy in promoting CO2 hydrogenation to olefin-rich C2+ hydrocarbons over the γ-Al2O3 supported bimetallic Fe-Cu catalysts. In this work, we aim to clarify such a synergy by investigating the structure, Fe-Cu interaction and catalyst surface properties through a series of characterizations. H2-TPR results show that the addition of Cu makes both Fe and Cu easier to reduce via the strong interaction between Fe and Cu, which is further confirmed by Fe K-edge X-ray absorption spectroscopy (XAS). TEM images reveal the presence of metallic Fe and Fe-Cu alloy phases in the reduced Fe-Cu(0.17) catalyst. Adsorbed CO species, bicarbonate and carbonate species, and the formate and formic acid species are observed on the Fe-Cu(0.17) catalyst by in situ DRIFTS. Through H2-TPD and CO2-TPD, the type and amount of chemisorbed H2 and CO2 species have been analyzed and correlated with the catalyst performance for CO2 hydrogenation to higher hydrocarbons. It is found that both the moderately and strongly adsorbed H2 and CO2 play an important role in enhancing CO2 conversion, C2+ selectivity and the olefin/paraffin ratio. The product distribution analysis suggests that the pathway for CO2 hydrogenation to hydrocarbons over Fe-Cu catalyst involves both an indirect route with CO as the intermediate and a direct CO2 hydrogenation route. The promotion effect of Cu on Fe deceases with the increase of Cu content in Fe-Cu.